2008
DOI: 10.1227/01.neu.0000317304.31579.17
|View full text |Cite
|
Sign up to set email alerts
|

Extent of Resection and Survival in Glioblastoma Multiforme

Abstract: Treatment bias was demonstrated regarding resection and second-line therapies. However, bias and imbalances were controllable in the cohorts available from the 5-aminolevulinic acid study so that the present data now provide Level 2b evidence (Oxford Centre for Evidence-based Medicine) that survival depends on complete resection of enhancing tumor in glioblastoma multiforme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
366
0
16

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 943 publications
(387 citation statements)
references
References 16 publications
5
366
0
16
Order By: Relevance
“…Residual tumor after surgical resection is an independent prognostic factor for survival. 4,6) Although complete tumor resection is desirable, gliomas often can be only partially resected in order to preserve brain function. Residual tumor cells inevitably recur within a certain interval even after intensive radiotherapy and chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Residual tumor after surgical resection is an independent prognostic factor for survival. 4,6) Although complete tumor resection is desirable, gliomas often can be only partially resected in order to preserve brain function. Residual tumor cells inevitably recur within a certain interval even after intensive radiotherapy and chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Surgery and RT are still considered the basic treatment, and can be complemented with chemotherapy [1][2][3][4]6,13,[15][16][17][18][19][20]. The present investigation revealed that survival time of patients from group 2 (11.9 months) was statistically superior to that of patients from group 1 (7.4 months).…”
Section: Discussionmentioning
confidence: 60%
“…This study aims at comparing the survival of supratentorial adult GBM patients operated on at public hospital with that of GBM patients operated on at the private hospital and observe, if besides the previously identified prognostic factors [1][2][3][4][5][6][7] , socioeconomic factors, as previous reported by several authors, interfere in the GBM patients' survival in Brazil [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Intraoperative fluorescence contrast agents have been frequently mentioned in the literature. They improve the visualization of brain tumors during surgery and support complete resection (22,23). Preoperative injection of carbocyanine-labeled GfM may facilitate the macroscopic detection of tumor (Fig.…”
Section: Discussionmentioning
confidence: 99%